A Numerical Method using Collocation Approach for the Solution of Volterra-Fredholm Integro-Differential Equations - G. Ajileye; F. A. Aminu (African Scientific Reports)
This paper consider collocation approach for the numerical solution of Volterra-Fredholm Integro-differential equation using collocation method. We transformed the problem into a system of linear algebraic equations and matrix inversion is adopted to solve the algebraic equations. We substituted the solution algebraic equations into the approximate equation to obtain the numerical result. Some numerical problems are solved to demonstrate the efficiency and consistency of the method.